Case Report-Primary Renal Lymphoma: A Rare Entity - K.M. Hiwale1 , Preeti Sahu2 , Sunita Vagha3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Kidney involvement is an under-recognized complication of both Hodgkin and non-Hodgkinlymphoma (NHL).1,2 Many patient presents with acute kidney injury in newly diagnosed NHL, but patientbeing diagnosed with primary renal NHL is very rare. As it rarely occurs, it may not be considered initiallyduring patient presentation. In patient presenting with idiopathic kidney failure along with non-specific painin abdomen, primary NHL must be kept in mind. Below we present a patient who presented with pain inabdomen and was later diagnosed as a rare case of primary renal NHL.Case History: A 65 year old male presented with the chief complaints of pain in abdomen since 2 monthsand history of nocturia 3-4 times at night and dribbling of urine since 1 month. There were no significantfindings on general and systemic examination. CT scan revealed a solitary renal mass of 90 × 85 × 61 mmin upper pole of left kidney. Patient underwent Radical Nephrectomy and on histopathology specimen wasdiagnosed as - Infiltration of Non-Hodgkins lymphoma in kidney. Primary renal NHL.Conclusion: Primary involvement of kidney in NHL is extremely rare entity which should be always keptas differential diagnosis in case of radiological suspicion of primary renal mass. NHL is diagnosed onhistopathological grounds and can be first proven by performing renal biopsies in order to start chemotherapywhich is the main modality in treatment of PRL. Recent immunohistochemical tests allow correct diagnosisand also helps in classifying renal lymphomas.